2021
DOI: 10.3390/ijms221910755
|View full text |Cite
|
Sign up to set email alerts
|

Design of Gelatin-Capped Plasmonic-Diatomite Nanoparticles with Enhanced Galunisertib Loading Capacity for Drug Delivery Applications

Abstract: Inorganic diatomite nanoparticles (DNPs) have gained increasing interest as drug delivery systems due to their porous structure, long half-life, thermal and chemical stability. Gold nanoparticles (AuNPs) provide DNPs with intriguing optical features that can be engineered and optimized for sensing and drug delivery applications. In this work, we combine DNPs with gelatin stabilized AuNPs for the development of an optical platform for Galunisertib delivery. To improve the DNP loading capacity, the hybrid platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…The biosensor LOD was 0.5 pM, and it is well to underline that this method can be easily combined to detect other biomolecules by the naked eye. Since the surrounding of the NPs affects the LSPR, and the LSPR peak wavelength shift is proportional to the changes in the refractive index of the surrounding, this property could be useful to estimate the thickness of a biopolymer wrapping NPs, as proposed by Tramontano et al [61]. The authors monitored the gelatin thickness on the surface of diatomite NPs due to the AuNPs grown in situ on their surface.…”
Section: Lspr-based Colorimetric Biosensorsmentioning
confidence: 99%
“…The biosensor LOD was 0.5 pM, and it is well to underline that this method can be easily combined to detect other biomolecules by the naked eye. Since the surrounding of the NPs affects the LSPR, and the LSPR peak wavelength shift is proportional to the changes in the refractive index of the surrounding, this property could be useful to estimate the thickness of a biopolymer wrapping NPs, as proposed by Tramontano et al [61]. The authors monitored the gelatin thickness on the surface of diatomite NPs due to the AuNPs grown in situ on their surface.…”
Section: Lspr-based Colorimetric Biosensorsmentioning
confidence: 99%
“…Tramontano, Manago et al have used gold-coated, gelatin-capped diatomite nanoparticles to improve the drug-loading capacity of the same [60,61]. The authors demonstrated that that the drug-loading capacity of these diatomite-based carriers can be enhanced and modulated as a function of the gelatin shells around the biosilica surface.…”
Section: Anticancer Organic Drugs Deliverymentioning
confidence: 99%
“…Furthermore, the gold coating confers remarkable properties to the carriers [62,63], allowing real-time monitoring of the drug release via near-field optical amplification of label-free sensing, with excellent specificity and sensitivity [61]. Full optical theoretical Tramontano, Manago et al have used gold-coated, gelatin-capped diatomite nanoparticles to improve the drug-loading capacity of the same [60,61]. The authors demonstrated that that the drug-loading capacity of these diatomite-based carriers can be enhanced and modulated as a function of the gelatin shells around the biosilica surface.…”
Section: Anticancer Organic Drugs Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…For in vitro release study, 1 mg of ICG-GNP-80 solution in 1 ml of PBS was prepared with or without 10 ml of trypsin solution to simulate the cancer microenviornment and incubated in an orbital shaker at 37 C and 100 rpm. [29][30][31] At different time intervals, samples were centrifuged to collect 500 ml aliquots from the supernatant. An equal amount of PBS with or without trypsin was added before placing the samples back in the incubator.…”
Section: Preparation and Characterization Of Icg-gnpsmentioning
confidence: 99%